Geographical distribution, climatic variability and thermo‐tolerance of Chagas disease vectors. Issue 8 (19th December 2014) - de la Vega, Gerardo J.; Medone, Paula; Ceccarelli, Soledad; Rabinovich, Jorge; Schilman, Pablo E.
<x xml:space="preserve">Abstract</x> Understanding the relationship between geographic range limits and physiological traits of vector species is under increasing demand to predict the potential effects of global warming, not only in terms of geographic distribution of vector species but also in terms of the risk of disease transmission. Like in many other insect species, the geographical distribution of Chagas' disease vectors is affected by temperature. This study examines, for the first time, the relationship between the limits of geographic distribution and thermo‐tolerance of the most important vectors of Chagas disease, Triatoma infestans in southern South America and Rhodnius prolixus in northern South America and Central America, to test the climatic variability hypothesis (CVH). We applied species distribution modeling (SDM) using bioclimatic variables and identified the most important limiting factors of the habitat suitability. Then, we measured and compared: the critical thermal maximum (CTmax) and the upper lethal temperature (ULT) (measured by thermo‐limit respirometry), chilled coma recovery (i.e. the time to recovery from 4 h at 0°C) and the critical thermal minimum (CTmin). For both species the minimum temperature of the coldest month was the most important abiotic factor restricting their geographic distribution. By taking a correlative approach and testing predictions with thermal tolerance traits, it was possible to explain the southern limit distribution for both species in terms of physiological constraints. The greater temperature tolerance of T. infestans compared to R. prolixus supports the CVH.